Escherichia coli Group 2 capsules and their interplay with bacteriophages - McGarry, Naoise; Toner-Bartelds, Catherine; Smith, Stephen G. J. (Frontiers in Microbiology, 2025)
IntroductionExtracellular polysaccharide capsules of Gram-negative bacteria, such as Escherichia coli (E. coli), mediate interactions with host defences and bacteriophages (phages). Capsules may act as barriers to infection or serve as essential receptors when phages rely on capsule recognition and degradation by depolymerases.MethodsIn this study, we examined the Group 2 K2 capsule of the extra-intestinal pathogenic E. coli (ExPEC) prototype CFT073 to determine its role in phage infection. We assessed whether the capsule acts as a barrier or receptor and explored the effect of temperature on such interactions. Additionally, we analysed E. coli genomes to identify whether capsule biosynthesis genes were co-located with other loci associated with phage defence. The evolutionary context of these associations was alsoc explored.ResultsThe K2 capsule of CFT073 exhibited dual functionality, acting both as a barrier to phage infection and as a receptor facilitating infection. A previously unrecognized synergy was observed between capsule expression and a type IV toxin–antitoxin (TA) system in CFT073. It was also shown that co-localisation of capsule and TA loci was present in more than 500 E. coli genomes, indicating a conserved association. Further, these systems were shown to be horizontally co-acquired on a common pathogenicity island.DiscussionThese findings highlight the complex role of capsules in phage interactions and suggest that their functional linkage with TA systems may enhance bacterial persistence. The conserved co-acquisition of these loci on pathogenicity islands underscores their potential importance in the evolution and success of ExPEC pathogens.